Green fertilizer: binder from chitosan, natural rubber & lignin - Mohamad, Noraiham; Mohamad Juoi, Jariah; Abd Razak, Jeefferie (Penerbit UTeM Press, 2023)
Chitosan, natural rubber and calcium lignosulfonate from lignin can be manipulated to replace formaldehyde in synthetic urea-formaldehyde fertilizer for slow release. Formaldehyde is highly toxic and can trigger the need for green fertilizers. This book explores the potential of natural biodegradable polymers to be blended with urea fertilizer.